Estudo e caracterização de ligas niti com efeito memória de forma - Moura, Danilo Maia (Universidade Federal Rural do Semi-Árido, 2017)
This work carried out the characterization of some materials in order to discover its real composition. The materials are alloys of the NiTi system with shape memory effect (EMF), we call EMF alloys that have as main characteristic to return to their original shape after undergoing some deformation due to a mechanical request. NiTi alloys have a certain advantage over cost because in all other alloys contain noble materials in their composition, except copper alloys, another factor that makes them advantageous is their biocompatibility for biomedical applications. These materials have little information in the market for some properties. The X-ray diffraction (XRD) was used to study the crystallography, microstructure analysis by Optical Microscopy (OM) in order to observe which phases are present in the alloy, analysis chemistry by X-ray Fluorescence Spectroscopy (EFRX) to conduct a study of chemical composition. Finally, the results were compared with the existing literature for a larger baseline.
Monografia
Keywords: Ni-Ti; Efeito memória de forma; Caracterização; Ni-Ti; Shape memory effect; Characterize; ENGENHARIAS::ENGENHARIA MECANICA